HUBUNGAN FUNGSI MANAJEMEN KEPALA RUANGAN DENGAN PELAKSANAAN PENGENDALIAN INFEKSI NOSOKOMIAL DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Edisyah Putra Ritonga; Nataria Yanti Silaban (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Nosocomial infection or Health Care-Associated Infection (HCAI) is an infection that occurs while a patient is receiving services at a health facility, where there are no signs of infection or symptoms of the patient being in an incubation period at the time of hospital admission. Nosocomial infections are hospital-acquired infections that occur in patients who are hospitalized for 72 hours. Nosocomial infections in 10 general education hospitals (RSU) in Indonesia are quite high, namely between 6-16% with an average of 9.8% in 2010. The purpose of this study was to determine the relationship between the management function of the head of the room and the implementation of nosocomial infection control in Imelda Indonesian Workers General Hospital Medan. This type of research is a quantitative study with a descriptive correlation research design. The population in this study were all nurses who were in Imelda Medan General Hospital, amounting to 75 people. the sample in this study were 43 nurses. Based on the results of the study, the relationship between the management function of the head of the room and the implementation of nosocomial infection control at Imelda Indonesian Workers General Hospital in Medan was p 0.000 < 0.05. This explains that there is a rejection of Ho or Ha is accepted so that it is concluded that there is a significant relationship between the management function of the head of the room and the implementation of nosocomial infection control.